Growth and yield responses of groundnut to different rates of NPK fertilizer at Umudike - Orji KO; Chukwu LA; Ogbu JU (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
The field trial was carried out in the 2014 cropping season in the Research and Training Farm (Eastern Farm) of the Michael Okpara University of Agriculture, Umudike to assess the effect of NPK 15: 15: 15 fertilizer rates on the biological and economic yields of groundnut (Ogoja spreading cultivar). The experiment was laid out in Randomized Complete Block Design (RCBD) with three replicates. Two viable seeds were sown at 40cm×40cm in a hole/hill along the crest of a 10m ridge with 0.5m spacing between two ridges on 28th June 2014. NPK 15:15:15 fertilizer was applied to each hill on 26th July at the rates of 0, 50, 100, 150, 200, and 250 kg/ha using the ring method. Field data were taken on the total fresh weight (g) of biomass/hill, number of pods/hill, fresh weight (g) of pods/hill, number of seeds/hill, 100 seeds` weight (kg/ha), and harvest index. The field data collected were subjected to Analysis of Variance (ANOVA), Coefficient of Variation (CV), and line graphs with error bars using Genstat 12 edition and Excel Package, respectively. Fisher`s list significant difference (F-LSD) was applied to detect a significant difference between two means (P= 0.05). The result showed that the soil was texturally sandy loam with a pH of 5.20. The soil was also low in organic matter, total nitrogen, and potassium. But, it was high in phosphorus and exchangeable acidity. The application of NPK fertilizer significantly influenced (P≤0.05) the total fresh weight of biomass of groundnut with 150kg/ha giving the highest total fresh weight of biomass/hill. In the same vein, the application of NPK fertilizer at 250kg/ha also significantly increased (P≤0.05) the number of pods/hill. However, NPK fertilizer application did not significantly affect (P≥0.05) the total fresh weight of pods/hill, number of seeds/hill, 100 seed weight/hill, and harvest index.